2011
DOI: 10.1002/mop.25796
|View full text |Cite
|
Sign up to set email alerts
|

A novel Minkowski‐island‐based fractal patch for dual‐mode and miniaturization band‐pass filters

Abstract: A miniaturized dual‐mode band‐pass filter (BPF) using Minkowski‐island‐based (MIB) fractal patch resonator is presented in this article. The BPF is mainly formed by a λg/4 square patch resonator, which is a MIB fractal configuration with second order iteration is embedded in the patch. By tuning the perturbation, which resulted from the fractal patch, two resonant modes are excited and a pair of transmission zeros are generated to improve the BPF performance. The proposed filter at center frequency (f0) of 630… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Analogized to the slot etched resonator , the crossed‐line patch resonator is proposed at first. Then, merged the crossed‐line patch resonator and the MIB fractal resonator , the crossed‐island patch resonator is obtained for improving the MIB fractal resonator. The dimensions of the square patch resonators are: (a) original patch: L 1 = 8.7mm, L 2 = 1.2mm, W 1 = 5.0mm, W 2 = 2.5mm, W 3 = 0.35mm,W 4 = 0.1mm, g = 0.1mm, and W p1 = W p2 = 1.45mm. (b) crossed‐line patch: L 1 = 8.7mm, L 2 = 2.4mm, W 1 = 3mm, W 2 = 2mm, W 3 = 0.5mm, W 4 = 0.2mm, W 5 = 0.25mm, W 6 = 4.38mm, W 7 = 3.09mm, g = 0.1mm, and W p1 = W p2 = 1.45mm (c) crossed‐island patch: L 1 = 8.7mm, L 2 = 4.0mm, W 1 = 3mm, W 2 = 2mm, W 3 = 0.3mm, W 4 = 0.25mm, W 5 = 0.26mm, W 6 = 4.36mm, W 7 = 3.08mm, W 8 = 0.9mm, W 9 = 0.9mm, g = 0.2mm, and W p1 = W p2 = 1.8mm. …”
Section: Dual‐mode Square Patch Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogized to the slot etched resonator , the crossed‐line patch resonator is proposed at first. Then, merged the crossed‐line patch resonator and the MIB fractal resonator , the crossed‐island patch resonator is obtained for improving the MIB fractal resonator. The dimensions of the square patch resonators are: (a) original patch: L 1 = 8.7mm, L 2 = 1.2mm, W 1 = 5.0mm, W 2 = 2.5mm, W 3 = 0.35mm,W 4 = 0.1mm, g = 0.1mm, and W p1 = W p2 = 1.45mm. (b) crossed‐line patch: L 1 = 8.7mm, L 2 = 2.4mm, W 1 = 3mm, W 2 = 2mm, W 3 = 0.5mm, W 4 = 0.2mm, W 5 = 0.25mm, W 6 = 4.38mm, W 7 = 3.09mm, g = 0.1mm, and W p1 = W p2 = 1.45mm (c) crossed‐island patch: L 1 = 8.7mm, L 2 = 4.0mm, W 1 = 3mm, W 2 = 2mm, W 3 = 0.3mm, W 4 = 0.25mm, W 5 = 0.26mm, W 6 = 4.36mm, W 7 = 3.08mm, W 8 = 0.9mm, W 9 = 0.9mm, g = 0.2mm, and W p1 = W p2 = 1.8mm. …”
Section: Dual‐mode Square Patch Resonatorsmentioning
confidence: 99%
“…Dual‐mode filters have been widely used in wireless communications systems because of their advantages in applications such as small size and low loss . There are several commonly used dual‐mode patch resonators including crossed slots , loaded crossed‐slots , right crossed‐slots , slot etched , and fractal configurations in a square patch. The arc‐oriented slot etched into a circular patch was used to design a dual‐mode dual‐band BPF .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, research work in this field has shown a dramatic increase. A variety of fractal geometries have been applied to design compact BPFs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the iteration order of Minkowski‐island‐based (MIB) fractal resonator, it indicated a miniaturized property. A second‐order MIB fractal resonator was used to design a high performance dual‐mode BPF at direct television (DTV) ultra high frequency (UHF) bands [11].…”
Section: Introductionmentioning
confidence: 99%
“…Merging the features of single‐feed aperture‐coupled stack antenna [1–4], orthogonal modes [6–8], dual‐mode of ring/loop resonators [9, 10], and MIB fractal resonator [11], a novel stack antenna constructed with a perturbed MIB fractal patch, an aperture‐coupled structure, and a straight‐strip feed line is proposed in this article. First, by increasing the iteration order of MIB fractal resonator, the resonant frequency can be moved toward the lower frequency, indicating a miniaturized property.…”
Section: Introductionmentioning
confidence: 99%